MEDIA UTILISATION AMONG SECONDARY TRAINEE TEACHERS IN THEIR TEACHING-LEARNING ACTIVITIES - R., RAMESH (International Journal of Research -GRANTHAALAYAH, 2021)
This study explored the views of teacher trainees on various components of their training about the use of new technology to teach their subject. There is a significant change in our daily life with the advancement of information and communication technologies. Integrating ICTs into teaching and learning offers significant potentials for higher education institutions and opens new challenges for educators, through their capacity to facilitate new kind of education in the digital environment. Particularly, the use of technology in teacher education opens new opportunities for teachers and students. The success of ICT in teacher education depends on teacher educators, trainee teachers and authorities in the institutions. The present study investigated the media utilisation among secondary trainee teachers in their teaching-learning activities. The investigator adopted the survey method and used random sampling technique for the selection of sample. A structured questionnaire was distributed to the selected 500 teacher-trainees and data collected were analyzed using t-test. The findings concluded that the selected personal variables like sex, locality of the students, type of institutions and locality of the institutions have influenced media utilisation among secondary trainee teachers in their teaching-learning activities.